2010
DOI: 10.1063/1.3339784
|View full text |Cite
|
Sign up to set email alerts
|

Size selected synthesis of CoFe2O4 nanoparticles prepared in a chitosan matrix

Abstract: In this paper we report the synthesis and magnetic properties of CoFe2O4 nanoparticles. The nanoparticles with sizes ranging from 6 to 20 nm were prepared in a chitosan matrix. Size selection was achieved by introducing a nonionic surfactant Tween-X, where X={20, 60, 80, and 85}. Aqueous dispersions of Tween-X show micelles with increasing hydrodynamic sizes as X increases. Mössbauer spectroscopy measurements at 300 K show superparamagnetic behavior for the small particles, changing gradually to a blocked magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…To explore the optical properties of the nanoparticles, the absorbance and uorescence spectroscopy is widely used. 63,64 Many investigators [65][66][67][68][69][70] have studied the optical characteristic of cerium oxide thin lms by utilizing UV-vis transmittance measurements. The deposition of material on the substrate to form thin lm generates interference effects and creates oscillations, which determine the spectra.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…To explore the optical properties of the nanoparticles, the absorbance and uorescence spectroscopy is widely used. 63,64 Many investigators [65][66][67][68][69][70] have studied the optical characteristic of cerium oxide thin lms by utilizing UV-vis transmittance measurements. The deposition of material on the substrate to form thin lm generates interference effects and creates oscillations, which determine the spectra.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…It is well-known that the CoFe 2 O 4 spinel oxide is a hard magnetic material with large coercivity and magnetization, making it an excellent candidate for technological applications. Its coercivity and squareness (defined as the remanence (M r ) normalized to the saturation magnetization (M S ), M r /M S ) is strongly size dependent. , Chinnasamy and co-workers found that for CoFe 2 O 4 particles the maximun value of the coercivity, H C ∼ 20 kOe, is reached for an average diameter of <ϕ> = 40 nm. Then the coercivity decreases to H C ∼ 10 kOe when the size is reduced down to <ϕ> = 8 nm.…”
Section: Introductionmentioning
confidence: 99%
“…CoFe 2 O 4 -CoFe 2 core-shell nanoparticles were obtained from a single-phase CoFe 2 O 4 powder prepared by an ionic coordination technique. 11 The average particle size for the CoFe 2 O 4 powder was obtained by using x-ray diffraction ͑XRD͒ microscopy and it was found to be 32 nm. CoFe 2 shells with different thicknesses were readily obtained by reducing CoFe 2 O 4 powder samples under a controlled hydrogen flux for various period of time ͑15, 30, 60, 90, and 120 min͒ at 300°C.…”
mentioning
confidence: 99%